The Courage to Lead: Leadership in the African American Urban Church - Harris, James Henry (Rowman & Littlefield Publishers, 2001)
This book focuses on pastoral and lay leadership in the African American church. It deals with the internal and external issues such as the tendency toward a bifurcated mentality and practice such as the 'this is business' syndrome as well as the social issue of race and affirmative action. Ministers and laity in the black church must actively engage themselves in overcoming the inequities that are still endemic to life in urban America. Harris affirms that affirmative action policies are more important than ever in obtaining a degree of social justice.